(untitled) (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: The effect of zeolite on Ca plasma concentration, reproductive parameters, body condition score (BCS), and colostrum properties was evaluated in Holstein dairy cows during the postpartum period. Materials and Methods: Sixty pregnant cows were allocated to three experimental groups, including 1) a control (CON) diet; 2) a CON diet + 0.75% dry matter (DM) zeolite (100 gm/day/ cow); and 3) a CON diet + 1.5% DM zeolite (200 gm/day/cow). Experimental diets were fed to cows during the last 4 weeks of pregnancy. Blood sample evaluation for Ca concentration was done. The prevalence of hypocalcemia and reproductive parameters, including BCS and colostrum properties, was also measured. Results: Total Ca and ionized calcium (Ca++) concentrations in plasma at 6 and 12 h after calving were higher in zeolite-consuming cows than those in CON s (p < 0.01). Mean frequencies for severe and subclinical hypocalcemia in zeolite-consuming cows were 11.64% and 19.36% lower than those in the CON group, respectively (p < 0.01). The mean pregnancy efficiency of these cows was also 12.94% higher than the CON (p < 0.01). The mean BCS (p ≤ 0.05) and colostrum quality (p < 0.01) of zeolite-consuming cows were at maximum, but their mean colostrum yield was lower than that of the CON group (p < 0.01). Conclusion: Zeolite dietary supplementation at levels of 0.75% and 1.5% DM of the periparturient diet is recommended for better CON of hypocalcemia, improved BCS and colostrum quality, and better prevention of postpartum reproductive disorders in dairy cows. J. Adv. Vet. Anim. Res., 10(3): 410–420, September 2023 http://doi.org/10.5455/javar.2023.j694